2021
DOI: 10.1037/spq0000443
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent academic worries amid COVID-19 and perspectives on pandemic-related changes in teacher and peer relations.

Abstract: Despite recognition of the potential impact of the COVID-19 pandemic on secondary schooling experiences, little empirical evidence has captured adolescents' perspectives on the extent of academic and social disruption resulting from the pandemic. The present study examined adolescents' academic worries amid the COVID-19 pandemic and their perspectives on pandemic-related changes in teacher and peer relations. Participants were 452 adolescents (55% female) between the ages of 11 and 17, who completed online sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 33 publications
7
49
1
Order By: Relevance
“…Moreover, adolescents were slightly more worried about COVID-19's academic and economic impact than about the family's financial situation. As such, in line with previous studies ( 13 , 14 ), our results underline the importance of addressing the impact of both school-related stress and the economic situation on adolescents' worries.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, adolescents were slightly more worried about COVID-19's academic and economic impact than about the family's financial situation. As such, in line with previous studies ( 13 , 14 ), our results underline the importance of addressing the impact of both school-related stress and the economic situation on adolescents' worries.…”
Section: Discussionsupporting
confidence: 92%
“…Recent research indicated that the most common COVID-19-related worries among adolescents are related to the impact of the restrictions on academic careers (i.e., college admissions) and health effects of an infection (i.e., self-infection and family illness) ( 13 ). Other research also identified academic worries as one type of worry related to the COVID-19 pandemic ( 14 ). However, research is still limited regarding the different content of worries and their relation to adolescent mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a recent study by Moser et al (2021) demonstrated that teachers expressed concerns about students’ achievements. Moreover, students felt a lack of consultation ( Korzycka et al, 2021 ) and decreased support from teachers ( Lessard and Puhl, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research has been conducted in general adult population above 18 years old (e. g. Boyraz et al, 2020 ; Ho et al, 2005 ; Moore & Lucas, 2020 ), while only a few studies have been carried out with particularly vulnerable populations (e.g., Maxfield & Pituch, 2020 ), healthcare workers (e.g., Puci et al, 2020 ) and people with chronically diseases (e.g., Joensen et al, 2020 ). There are some recent studies that have examined worries about COVID in adolescents (e.g., Jamieson et al, 2021 ; Lessard & Puhl, 2021 ; Vogel et al, 2021 ) and young people (e.g., Lehmann et al, 2021 ; Shukla et al, 2021 ; Yıldırım et al, 2020 ), stressing that concerns about the pandemic have a considerable impact on the negative affectivity of adolescents and young adults.…”
mentioning
confidence: 99%